2013
DOI: 10.1111/jbi.12094
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between limb reduction, body elongation and geographical range in lizards (Lerista,Scincidae)

Abstract: Aim The relationship between changes in body form (limb reduction and body elongation) and geographical range size was investigated across 68 species of Lerista, a species‐rich clade of Australian scincid lizards that exhibits extensive interspecific variability in both body form and range size. Location Lerista occurs across the entire Australian mainland, with diversity concentrated in arid and semi‐arid regions. Methods Geographical range size was estimated directly from c. 14,000 museum specimens using bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…While the heritability of range size has been demonstrated for many lineages, possible mechanistic explanations have varied, and include niche breadth [27], dispersal ability [76, 77], and morphological characteristics [26, 78] of lineages, as well as the geographic limits of biomes, landmasses, or hydrological basins [79]. In many cases, these factors may be interlinked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the heritability of range size has been demonstrated for many lineages, possible mechanistic explanations have varied, and include niche breadth [27], dispersal ability [76, 77], and morphological characteristics [26, 78] of lineages, as well as the geographic limits of biomes, landmasses, or hydrological basins [79]. In many cases, these factors may be interlinked.…”
Section: Discussionmentioning
confidence: 99%
“…The heritability of range size has been a matter of debate, but increasing numbers of studies demonstrate its heritability [2125]. In at least some clades, including lizards, this heritability is associated with variable morphological or ecological traits [26, 27]. Likewise, numerous studies have reported trait-associated variation in diversification rates, especially since the development of BiSSE (binary-state speciation and extinction) and related models [28].…”
Section: Introductionmentioning
confidence: 99%
“…B) may suggest morphologically induced dispersal costs (Gaston and Blackburn , Agosta et al ). Exemplifying this case, Lee et al () found that while typical lizards showed both big and small ranges, limbless ones showed only smaller ranges. The lower bounds of such relationships can be imposed by the minimum measuring unit size (e.g.…”
mentioning
confidence: 98%
“…The low energetic requirements and often relatively small size of terrestrial ectothermic animals raise the question of whether energetic requirements would be an important correlate of range size, or if dispersal costs might be more important. The limited evidence available on this topic is still conflicting, with some studies showing significant relationships between body size and range size, whereas others not (Taylor and Gotelli , reviewed by Gaston and Blackburn , Lee et al , see Discussion). This evidence mostly comes from unifactorial studies that did not control for phylogenetic relationships in the tests or any kind of uncertainties.…”
mentioning
confidence: 99%
“…Research has shown the development of limblessness within this genus to have occurred a number of times and is an unusually plastic condition, with a variety of conditions sometimes occurring within the same species (Amey & Worthington Wilmer 2014;Skinner 2010). The value of this situation in the study of limb loss has long been recognised (Benesch & Withers 2002;Greer 1987Greer , 1990Greer , 1992Lee et al 2013;Skinner 2010).…”
Section: Introductionmentioning
confidence: 99%